Pengaruh Faktor Internal dan Eksternal Petani terhadap Pencegahan Kebakaran Lahan Gambut - Robi Deslia Waldi; Bambang Hero Saharjo; Israr Albar (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2019)
Peat fire prevention activities conducted by farmers as a form of they role in realizing sustainable agriculture. Sustainable agriculture can be run as to maximizing internal factors such as age, formal education, income, land area, land status, distance of land location and exsternal factors such as interaction with instructor or instructor instructors, community leaders, involvement in farmer groups, information media, and government roles. Using SPSS 25 with validity in order test to test the level of relationship and validity, validity by looking at r count > r table which called then valid and if r count < r table then called invalid and reliability tests to know reliable, if the reliability coefficient is Alpha Cronbach is more than 0.70 (ri> 0.70) and should not be more than 0.90 (ri <0.9). Result of research shown that The Internal and external factors still have a relatively low level connection, because the facilities and infrastructures are not maximized to support sustainable agricultural development. Meanwhile internal factors that have a real relationship are age and formal education while external factors that have a real relationship are involvement in farmer groups, information media, and communication and the role of government. Key words: exsternal factors, internal factors, peat fire prevention, sustainable agriculture